2020
DOI: 10.1590/1806-9282.66.12.1628
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hot flashes in women of 40 to 65 years of age with metabolic syndrome

Abstract: SUMMARY OBJECTIVE: Hot flashes have a negative impact on the quality of life of women during the menopausal transition and thereafter. The progressive reduction in gonadal estrogen levels associated with aging promotes an accumulation of abdominal fat, dyslipidemia, and arterial hypertension, all of which are components of metabolic syndrome (MetS). The objective of the present study was to estimate the prevalence of hot flashes and evaluate their relationship with MetS in women ≥ 40 years of age. METHODS: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…As shown by Karim et al, higher ghrelin concentrations are positively correlated with a greater likelihood of hot flashes in women in the early and late postmenopausal period [ 39 ]. Based on their research, Sau et al suggest a relationship between hot flashes and the occurrence of metabolic syndrome in women aged 40–65 [ 12 ]. Also, Kazama et al showed that the fat mass index was positively associated with severe hot flashes, whereas the lean mass index was negatively correlated [ 40 ].…”
Section: Adipocyte-derived Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Karim et al, higher ghrelin concentrations are positively correlated with a greater likelihood of hot flashes in women in the early and late postmenopausal period [ 39 ]. Based on their research, Sau et al suggest a relationship between hot flashes and the occurrence of metabolic syndrome in women aged 40–65 [ 12 ]. Also, Kazama et al showed that the fat mass index was positively associated with severe hot flashes, whereas the lean mass index was negatively correlated [ 40 ].…”
Section: Adipocyte-derived Hormonesmentioning
confidence: 99%
“…The frequency of hot flash episodes varies from occasional attacks in a week or day to at least one every hour [ 2 , 8 , 10 , 11 ]. Hot flashes are often associated with impairments in quality of life, loss of productivity, depressed mood, embarrassment, fatigue, anxiety, sleep disturbance, and possibly even poorer memory function and social isolation [ 4 , 7 , 12 ]. The physiological and molecular mechanism of hot flashes is still incompletely known.…”
Section: Introductionmentioning
confidence: 99%
“…Progressive estrogens deprivation may also cause hot-flashes accompanied metabolic dysfunctions like increased abdominal fat, dyslipidemia, arterial hypertension (39). One study from 2020 showed a statistically significant correlation between hot flashes and metabolic syndrome in women over 40 years (39).…”
Section: Hot Flashes -Associated Elementsmentioning
confidence: 99%
“…Progressive estrogens deprivation may also cause hot-flashes accompanied metabolic dysfunctions like increased abdominal fat, dyslipidemia, arterial hypertension (39). One study from 2020 showed a statistically significant correlation between hot flashes and metabolic syndrome in women over 40 years (39). Weight control (meaning weight loss in females with increased body mass index) during menopausal transition might be a double hit for both controlling the hot flashes and metabolic anomalies, although hot flashes equally affect normal weighted women (40).…”
Section: Hot Flashes -Associated Elementsmentioning
confidence: 99%